A home gardening training programme to alleviate household food insecurity for low income household dwellers - Lekotoko, Queen Lebogang (My University, 2008)
INTRODUCTION: Urban agriculture (UA) is increasingly being seen as an important component of urban development and urban environmental management. Urban agriculture is an alternative source of employment, household income, food and nutrition security among many low-income urban dwellers. Investments in Urban agriculture in South Africa are negatively influenced by a paucity of information on available land and farming opportunities and lack of policy. A situation analysis in Eatonside concluded that high unemployment rates, income-poverty, chronic household food insecurity and a high prevalence of malnutrition existed. Efforts to increase food availability will bring overall benefits to the community. OBJECTIVES: The main objective of this project was to conduct an empirical study to assess food insecurity training needs in order to develop an appropriate home gardening training programme for gardeners in the informal settlements. METHODS: A random selection of 143 households was made from the informal settlement (refer baseline), but only 91 dwellers successfully completed the questionnaires that were administered by four trained field workers. The resu Its were analysed using the SPSS® 12.0 program. MAJOR FINDINGS AND IMPLICATIONS: The results showed that 72.5 percent had some knowledge of home gardening, whereas 29.7 percent had skills at all in home gardening; 69.2 percent responded that they had some knowledge of soil management, while 69.2 percent had no knowledge regarding planting management and only 13.2 percent had any knowledge regarding storage after harvesting and preparation of vegetables. Out of all the 91 participants, only 29.7 percent had ever worked in a garden. The researcher and fieldworkers were the first group to be trained so that they could conduct the training of the participants with the assistance of the farmers. Since the patiicipants were both male and female, no problems were encountered with digging the ground, as every day after training the males made a point of preparing the ground for the next day. Training was conducted over two days for each group; there were four groups including the fieldworkers. Groups 2 and 3 had 25 participants each while group 4 had 41 participants (n = 91). On day one, the trainers provided all the theory that the participants would need to work in a garden. On day two, the trainers incorporated theory with practical training which involved the participants. CONCLUSION It was found that most of the householders who participated in this project owned a vegetable garden. Most of the participants felt that they had benefited greatly from the training given in the gardening project, both because they were now able to have year round access to fresh vegetables, and because of the money-saving aspect
M. Tech. (Food Service Management, Department of Hospitality and Tourism, Faculty of Human Sciences) -- Vaal University of Technology|
Keywords: Urban agriculture; Food and nutrition security; food insecurity; Home gardening; Vegetable gardens; 635; Food crops; Nutrition -- South Africa